Emerging Role of the Fibroblast Growth Factor 23/Klotho Axis in Cardiovascular and Metabolic Conditions:A Narrative Review - Berezin, A. E.; Pavlov, S. V.; Pakholchuk, O. P.; Березін, Олександр Євгенійович; Павлов, Сергій Васильович; Пахольчук, Ольга Петрівна (My University, 2020)
Klotho protein is a powerful regulator of various metabolic pathways including endothelial integration, cell adaptation processes, ion transport, signal transduction, regulation of calcium, potassium, parathyroid hormone, phosphates and glucose metabolism, and reduction of oxidative stress. Klotho protein ensures its biological effects through binding with fibroblast growth factor (FGF)-23 and altered Klotho/FGF23 axis was found a core element in the pathogenesis of the cardiovascular and metabolic disease. It has been found that predisposition for CV disease can be related to Klotho gene polymorphism, while the clinical significance of this finding is required to be elucidated in large clinical studies. The aim of the review was to summarize findings regarding the role of the FGF23/Klotho axis in the CV and metabolic conditions, as well as to identify perspectives to use Klotho protein as a promising pharmacological target for personifying therapy.
Keywords: Klotho; fibroblast growth factor-23; biomarkers; cardiovascular disease; metabolic disease